Peran Bedah Rekonstruksi Uretra dalam Memulihkan Fungsi Reproduksi pada Pria dengan Cedera Urogenital - Basalamah, Muhammad Fachrurrozy; Suryoadji, Kemal Akbar; Surya Putra, Abdul Hafiidh (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2024)
Background: This review evaluates urethral reconstruction’s effectiveness in fertility restoration. Methods: A systematic review was conducted using PubMed, Scopus, and Cochrane databases. Studies on anastomotic urethroplasty, buccal mucosa graft (BMG) urethroplasty, and acellular dermal matrix (ADM) grafts were analyzed. Outcomes included patency rates, ejaculatory function, erectile function, and fertility restoration, along with postoperative complications and long-term reproductive outcomes. Results: Anastomotic urethroplasty achieved >90% patency for strictures <2 cm, with 100% antegrade ejaculation restoration in pelvic fracture cases. BMG urethroplasty showed an 85.7–100% success rate for strictures >3 cm, with 76% reporting improved ejaculation force. ADM grafts had a 94% success rate in complex cases. Erectile dysfunction occurred in 9.7% but resolved within 6–20 months. Discussion: Urethral reconstruction restores patency and ejaculation in >85% of cases, but fertility outcomes depend on factors like testicular atrophy and neurovascular integrity. Non-transecting techniques reduce vascular complications, and early intervention aids spermatogenesis preservation. A multidisciplinary approach integrating andrology and assisted reproductive techniques is crucial.